Perkembangan Akhir Masa Anak-Anak - Azhariah Fatya; Sabrina Nurul; Linda Yarni (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Late childhood or what is known as elementary school age (SD) is a period of life development that lasts from the age of six until a child moves into adolescence and becomes sexually mature. The end of childhood is marked by dominant situations that can influence the child's personal adjustment and social adjustment. The research uses a critical review method by reading various books, journals or other publications related to the research topic discussed. The journals chosen consist of national and international journals, as well as several official websites. The research source comes from articles obtained via the internet in the form of research articles discussing late childhood development. The research results are as follows; a) Cognitive development is a person's ability to acquire, process and use information obtained from the surrounding environment b) Piaget and named the second level of moral development at the end of childhood as the level of conventional morality or morality from conventional rules and adjustments. c) Implications for children's end-of-life development in counseling services which aim to help them get to know themselves, develop their potential, overcome difficulties, and prepare children's mental and social development, as well as overcome problems experienced by children such as obstacles, disturbances and difficulties.